ChemInform Abstract: Stereoselective Synthesis of Arylglycine Derivatives via Palladium‐Catalyzed α‐Arylation of a Chiral Nickel(II) Glycinate. Issue 36 (September 2015) - Zhang, Fan; Sun, Hengzhi; Song, Zhuang; Zhou, Shuxi; Wen, Xiaoan; Xu, Qing‐Long; Sun, Hongbin
Abstract Structurally diverse aryl bromides are well tolerated in the α‐arylation reaction with a chiral nickel(II) glycinate complex.